Uniform convergence of the eigenfunction expansions of distributions associated with the polyharmonic operator on closed domain - Rakhimov, Abdumalik; Mohd Aslam, Siti Nor Aini (IOP Publishing Ltd., 2018)
In the solving the boundary value problems of equations of mathematical physics in bounded domains it is important to adjust the solution on the closed domain. This leads to the investigation of convergence and sumability problems near the boundary of the domain. In the present paper we study this problem for the eigenfunction expansions associated with the polyharmonic operator.